DAMPAK COVID-19 TERHADAP PENURUNAN VOLUME PENJUALAN DAN PENDAPATAN PEDAGANG DAGING AYAM BROILER (THE IMPACT OF COVID-19 ON THE DECLINE OF SALES VOLUME AND INCOME OF BROILER MEAT TRADERS) - Nina Regina Prayoga; Reny Sukmawani; Ema Hilma Meilani (Fakultas Pertanian Universitas Majalengka, 2021)
The Covid-19 pandemic has had a socio-economic impact in Indonesia, including broiler meat traders. Since the enactment of large-scale restrictions has triggered a lack of community activity outside, resulting in a decrease in sales volume and income at the Tipar Gede Warehouse Market, Sukabumi City. This study aims to determine the impact of COVID-19 on the decline in sales volume and income of broiler meat traders at the Tipar Gede Warehouse Market, Sukabumi City. This research was carried out using descriptive research with survey method research methods by describing the conditions or phenomena that occurred. From the research carried out, it was found that the impact of Covid-19 on sales volume before Covid-19 could be represented by 65%, while during Covid-19 there was a 35% decrease in sales volume and the impact of Covid-19 on the decline in income of broiler meat traders in Indonesia. The Tipar Gede Warehouse Market in Sukanumi City before Covid-19 was 60%, while during Covid-19 it was around 40%.